2017
DOI: 10.1088/0253-6102/68/1/29
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Quantum Correlations in Qubit-Qutrit Systems under the non-Markovian Environment

Abstract: We investigate the time evolution of quantum correlations of a hybrid qubit-qutrit system under the classical Ornstein-Uhlenbeck (OU) noise. Here we consider two different one-parameter families of qubit-qutrit states which independently interact with the non-Markovian reservoirs. A comparison with the Markovian dynamics reveals that for the same set of initial condition parameters, the non-Markovian behavior of the environment plays an important role in the enhancement of the survival time of quantum correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…(21) and depends on the specific choice of the CSF via the function χ(t) (Eqs. (26) and (27)). With these density matrices in our hand, we can then investigate the dynamics of entanglement by employing the tripartite negativity as given in Eq.…”
Section: A Independent Environments (Ies)mentioning
confidence: 98%
See 1 more Smart Citation
“…(21) and depends on the specific choice of the CSF via the function χ(t) (Eqs. (26) and (27)). With these density matrices in our hand, we can then investigate the dynamics of entanglement by employing the tripartite negativity as given in Eq.…”
Section: A Independent Environments (Ies)mentioning
confidence: 98%
“…In recent year, the dynamics of quantum correlations in the situation where quantum systems are affected by environments describes classically (i.e., model by means of a classical Gaussian or non-Gaussian distributed random field) has been an active area of research [6,7,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] and many interesting results have been obtained. In particular, it has been shown that when three qubits are coupled to an external classical noise such as random telegraph noise [16][17][18], static noise [20] and colored noise [19,21] in a common environment, quantum correlations among them survive indefinitely.…”
Section: Introductionmentioning
confidence: 99%
“…The corresponding evolution matrix of the subsystems is given by U (c 1 (t) , c 2 (t) ,t) = exp(− i H (t ) dt ) (hereafter = 1). The system is initially prepared in the one-parameter family state [50][51][52] given by…”
Section: Physical Modelmentioning
confidence: 99%
“…[17][18][19] Hence, many analytical tools, simulation techniques and several other methods for calculating and quantifying quantum correlations have been investigated to explore the separability of bipartite quantum systems. [20,21] Importantly, recent works shed light on studying quantum correlations for qubit-qutrit and qutritqutrit states, [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] which creates a fascinating future in quantum technologies. [39] Due to the possibility of maximum control of the associated Hilbert space, hybrid qubit-qudit systems have become increasingly important in the field of quantum information.…”
Section: Introductionmentioning
confidence: 99%